THE INCENTIVE IMPERATIVE: WHY PERFORMANCE BASED REWARDS OUTPERFORM TRADITIONAL COMPENSATION IN RETAINING PUBLIC SECTOR TALENT - Bako, Yasmin Sani; Abubakar, Hadiza Saidu; Gambo, Nasamu (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Despite widespread use of fixed benefits and promotion based compensation in public sectors, evidence on their relative effectiveness for talent retention remains limited. This study compares the retention impact of three compensation dimensions (benefits, promotion, incentives) in Nigerian public sector organizations experiencing 38% turnover increases. Using hierarchical regression analysis with data from 335 employees across seven judicial institutions, we demonstrate that performance based incentives substantially outperform traditional approaches. Incentives predict 14.4% of retention variance beyond all other factors (β = 0.38, p < 0.001), nearly triple the effect of benefits (β = 0.21) and more than triple promotion effects (β = 0.12). When transformational leadership moderates incentive delivery, effects strengthen by 45% (interaction β = 0.17, p < 0.001), whereas leadership cannot enhance dysfunctional promotion systems. The incentive advantage persists across both psychological retention (commitment, intentions) and behavioral retention (actual turnover), whereas promotion affects only intentions. We identify four mechanisms explaining incentive superiority: immediate reinforcement, clear effort reward linkages, frequent recognition opportunities, and personalization potential. These findings challenge public administration assumptions favoring standardized, seniority based compensation by demonstrating that performance differentiation through incentives achieves superior retention while requiring lower fixed costs than salary increases or expanded benefits. For resource constrained public sectors globally, prioritizing incentive investments over traditional compensation enhancements offers evidence based pathways to retention improvement.